Current research for a vaccine against Lassa hemorrhagic fever virus - Warner BM; Safronetz D; Stein DR (Dove Medical Press, 2018)
Bryce M Warner,1 David Safronetz,2 Derek R Stein2 1Department of Medical Microbiology, University of Manitoba, Winnipeg, MB, Canada; 2Zoonotic Diseases and Special Pathogens Program, National Microbiology Laboratory, Public Health Agency of Canada, Winnipeg, MB, Canada Abstract: Lassa virus (LASV) is a rodent-borne arenavirus endemic to several West African countries that causes Lassa fever (LF). LF is typically mild but it can cause severe disease characterized by hemorrhagic fever and multi-organ failure. A current outbreak of LASV in Nigeria has seen greater than 300 cases with a case fatality rate of 22%. Currently, there are limited treatment options and no vaccine candidates are approved to prevent LASV infection. The Coalition for Epidemic Preparedness Innovations has identified LASV as an emerging pathogen of high consequence and this has resulted in a push for several preclinical vaccine candidates to be advanced toward clinical trials. Here, we discuss several important aspects of LASV infection including immunobiology, immune evasion, and correlates of protection against LF, which have been identified through animal models and human infections. In addition, we discuss several vaccine candidates that have shown efficacy in animal models that could be advanced toward clinical trials. The increased fatality rate seen in the recent LASV outbreak in Nigeria highlights the importance of developing effective treatment and prevention strategies against LF. The spike in LASV cases seen in West Africa has the potential for increased mortality and human-to-human transmission, making the development and testing of effective vaccines for LASV critical. Keywords: Lassa virus, Lassa fever, vaccine, therapeutics, prevention, pathogenesis